An interesting case of Posterior Layering in the Urinary bladder on Fluorine- 18 Fluorodeoxyglucose (F18-FDG) PET-CT study - Farhana, Sharmin; Sifat, Taslima; Mia, Shohag; Quddus, Ruhul; Khan, Biva S; Islam, Saiful; Hussain, Raihan; Kabir, MF (Pulse, 2023)
Contrast PET/CT may show layering within the UB, and several examples of have been reported in the literature. But without using contrast this is rare. Our case demonstrates the interesting posterior layering of F18-FDG in urinary bladder in a 78 years old male without the use of contrast. Pulse Volume 12-14 2020-2022 p.32-33